Knowledge, attitude and prevention measures of students towards cutaneous leishmaniasis in Delanta district, Northeast Ethiopia. (May 2022) - Dires, Abebe; Kumar, Prem; Gedamu, Sisay; Yimam, Wondosen; Ademe, Sewunet
Abstract: Background and aims: Leishmaniasis is a neglected tropical disease which causes significant morbidity and mortality, particularly in developing countries. Cutaneous leishmaniasis (CL) is the main form of leishmaniasis that affects the skin. Knowledge and perception of people about leishmaniasis has a great impact to prevent the disease in endemic areas. Hence, the aim of this study was to assess the knowledge, attitude and preventive measures of Wegeltena secondary school students towards CL in Delanta district, one of the endemic areas in Northeast Ethiopia. Methods: A facility-based cross-sectional study was conducted from January 4 to 20, 2021 at Wegeltena secondary school in Delanta district, Northeast Ethiopia. A pre-tested, interviewer administered structured questionnaire was used to collect the data. Multivariable logistic regression analysis was utilized to measure the degree of association between outcome and independent variables. Statistically significant association with the outcome variables was declared at a p -value of <0.05. Results: A total of 388 students were participated in the study. In overall, 27.6% and 34.5% of participants had good knowledge and favorable attitude towards CL, respectively. Being grade 12 (AOR = 2.56; 95% CI: 1.23–5.29) and dwelling in urban areas (AOR = 1.78; 95% CI: 1.09–2.89) were determinants of good knowledge. However, female sex (AOR = 1.96; 95% CI: 1.21–3.18) and had good knowledge about CL (AOR = 3.75; 95% CI: 2.26–6.21) were significantly associated with favorable attitude of respondents towards the disease. Conclusion: In this study, nearly three-fourth of participants had poor knowledge about CL and two-third of them had unfavorable attitude towards the disease. Level of education and residence were determinants of respondents' knowledge about CL. Moreover, sex and level of knowledge about CL were determinants of respondents' attitude towards the disease. Therefore, an intensified health education program shall be implemented in schools that are found in endemic areas.